The beet cyst nematode Heterodera schachtii modulates the expression of WRKY transcription factors in syncytia to favour its development in Arabidopsis roots. - Muhammad Amjad Ali; Krzysztof Wieczorek; David P Kreil; Holger Bohlmann (PLoS ONE)
Cyst nematodes invade the roots of their host plants as second stage juveniles and induce a syncytium which is the only source of nutrients throughout their life. A recent transcriptome analysis of syncytia induced by the beet cyst nematode Heterodera schachtii in Arabidopsis roots has shown that thousands of genes are up-regulated or down-regulated in syncytia as compared to root segments from uninfected plants. Among the down-regulated genes are many which code for WRKY transcription factors. Arabidopsis contains 66 WRKY genes with 59 represented by the ATH1 GeneChip. Of these, 28 were significantly down-regulated and 6 up-regulated in syncytia as compared to control root segments. We have studied here the down-regulated genes WRKY6, WRKY11, WRKY17 and WRKY33 in detail. We confirmed the down-regulation in syncytia with promoter::GUS lines. Using various overexpression lines and mutants it was shown that the down-regulation of these WRKY genes is important for nematode development, probably through interfering with plant defense reactions. In case of WRKY33, this might involve the production of the phytoalexin camalexin.